Risk factors and mortality in patients with sepsis, septic and non septic acute kidney injury in ICU - Pinheiro, Kellen Hyde Elias (Sociedade Brasileira de Nefrologia, 2019)

(untitled) (J Bras Nefrol)
Acute kidney injury (AKI) has an incidence rate of 5-6% among intensive care unit (ICU) patients and sepsis is the most frequent etiology. AIMS: To assess patients in the ICU that developed AKI, AKI on chronic kidney disease (CKD), and/or sepsis, and identify the risk factors and outcomes of these diseases. METHODS: A prospective observational cohort quantitative study that included patients who stayed in the ICU > 48 hours and had not been on dialysis previously was carried out. RESULTS: 302 patients were included and divided into: no sepsis and no AKI (nsnAKI), sepsis alone (S), septic AKI (sAKI), non-septic AKI (nsAKI), septic AKI on CKD (sAKI/CKD), and non-septic AKI on CKD (nsAKI/CKD). It was observed that 94% of the patients developed some degree of AKI. Kidney Disease Improving Global Outcomes (KDIGO) stage 3 was predominant in the septic groups (p = 0.018). Nephrologist follow-up in the non-septic patients was only 23% vs. 54% in the septic groups (p < 0.001). Dialysis was performed in 8% of the non-septic and 37% of the septic groups (p < 0.001). Mechanical ventilation (MV) requirement was higher in the septic groups (p < 0.001). Mortality was 38 and 39% in the sAKI and sAKI/CKD groups vs 16% and 0% in the nsAKI and nsAKI/CKD groups, respectively (p < 0.001). CONCLUSIONS: Patients with sAKI and sAKI/CKD had worse prognosis than those with nsAKI and nsAKI/CKD. The nephrologist was not contacted in a large number of AKI cases, except for KDIGO stage 3, which directly influenced mortality rates. The urine output was considerably impaired, ICU stay was longer, use of MV and mortality were higher when kidney injury was combined with sepsis.